Agroecological practices in plants adopted by family farmers of the agricultural field fomento in Codó, Maranhão (Research, Society and Development, 2020)
In pursuit of a sustainable production system, agroecology emerges as a viable alternative for family farmers. Aiming at intensifying agroecological production, the objective of this work was to evaluate the practices of agroecological bases applied to vegetable cultivation at the Association of Small Producers of Campo Agrícola Fomento, located in the municipality of Codó, Maranhão. The research was developed between April and July 2018. Two types of procedures were adopted, where the first involved the case study method in descriptive research with quantitative and qualitative observation, in which the data collection instruments were performed through the application of semi-structured questionnaires, interviews, visits and conducting participatory meetings. The second procedure was adopted the extension practice to which educational lectures were held with the themes: composting and natural defenses. According to the questionnaire analyzes, when asked about the meaning of an agricultural system based on agroecology, 56% of respondents said they did not know and 44% said they knew the definition. The agroecological practices used by family farmers are organic fertilization, intercropping, mulching, and crop rotation. Thus, farmers do not classify their garden as organic but rather as an agro-ecological vegetable garden, because they use sustainable practices in the production of their vegetables, but sometimes when necessary use the use of chemical inputs.